2018
DOI: 10.1007/s11356-018-1314-x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Lu(III) sorbed on 2-line ferrihydrite at pH 5.7 and aged for 12 years at room temperature. I: insights from ICP-OES, XRD, ESEM, AsFlFFF/ICP-MS, and EXAFS spectroscopy

Abstract: Two-line ferrihydrite (2LFh) was aged for 12 years under ambient conditions and sheltered from light in the presence of Lu(III) used as surrogate for trivalent actinides. 2LFh aging produced hematite rhombohedra with overgrown acicular goethite particles. Analysis of the homogeneous suspension by asymmetrical flow field-flow fractionation (AsFlFFF) coupled to ICP-MS indicated that particles have a mean hydrodynamic diameter of about 140 nm and the strong correlation of the Fe and Lu fractograms hinted at a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Finck et al 27 reported that Lu, one of HREEs, incorporation in hematite and goethite after Lu coprecipitated with ferrihydrite was aged for 12 years at room temperature. 27 LREEs and HREEs behaved incoherently due to the subtle difference of their effective radii and affinities to iron oxides.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finck et al 27 reported that Lu, one of HREEs, incorporation in hematite and goethite after Lu coprecipitated with ferrihydrite was aged for 12 years at room temperature. 27 LREEs and HREEs behaved incoherently due to the subtle difference of their effective radii and affinities to iron oxides.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Finck et al 27 reported that Lu, one of HREEs, incorporation in hematite and goethite after Lu coprecipitated with ferrihydrite was aged for 12 years at room temperature. 27 LREEs and HREEs behaved incoherently due to the subtle difference of their effective radii and affinities to iron oxides. The ionic radii of REE(III) decrease from La 3+ (1.032 Å, 6coordination) to Lu 3+ (0.861 Å, 6-coordination), which are larger than those of Fe 3+ (0.645 Å, 6-coordination).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ferrihydrite exhibits a high adsorption capacity for various metal(loid) ions, it is metastable and gradually transforms into secondary minerals, including hematite and goethite (Finck et al, 2019). Hematite is formed by dehydration and reorganization among ferrihydrite particles (Wang et al, 2015a), whereas goethite is formed by ferrihydrite dissolution and reprecipitation (Shen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%